Relationship Between Adolescent Girls' Knowledge About Breast Cancer And Awareness Behaviour At SMA Negeri 2 Lubuk Linggau City - Yani, Putri Ari; Rossita , Taufianie; Ayudiah, Febra (Social Sciences Journal, 2025)
Data from the World Health Organisation (WHO), in 2021 worldwide there were seven million breast cancer patients. Breast cancer is the most common case suffered by women ... Based on data from the Indonesian Health Profile in 2020, breast cancer cases in Indonesia were 2.98% or estimated to be around 15,102 people, in 2021 there was an increase of 16.7% or estimated to be around 58,256 people (Kementrian Kesehatan RI, 2021). The method used was analytical research design with a cross-sectional approach, data were collected by distributing questionnaires to 77 respondents using proportional random sampling technique.The results of the univariate test analysis that almost half of the respondents (27.3%) had sufficient knowledge, and some respondents (51.9%) had unsupportive behaviour towards Sadari. The results of bivariate analysis showed that there was a significant relationship between knowledge and Sadari behaviour in adolescents where the value of p=0.004 was obtained. It is hoped that the school will collaborate with health workers to provide counselling on SADARI to detect breast cancer early.